Pengaruh Adopsi Artificial Intelligence dan Self-Learning terhadap Kinerja Pegawai pada Sektor Publik - Khalil Gibran; Fakhrurrazi Fakhrurrazi; Rio Putra Ramadhani; Mulia Andirfa; Al Mahfud Saputra (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the effects of Artificial Intelligence (AI) adoption and self-learning on the performance of public sector employees at the Pidie Jaya Regent's Office. This study employed a quantitative approach using a survey method involving all 66 employees through a saturated sampling technique. Data were analyzed using multiple linear regression with SPSS. The results indicate that Artificial Intelligence (AI) adoption has a positive and significant effect on employee performance (β = 0.387; t = 4.680; Sig. = 0.000). Likewise, self-learning has a positive and significant effect (β = 0.521; t = 7.017; Sig. = 0.000) and is identified as the most influential variable. Simultaneously, both variables have a positive and significant effect on employee performance (F = 163.734; Sig. = 0.000), with an Adjusted R² of 0.834, indicating that 83.4% of the variance in employee performance is explained by Artificial Intelligence (AI) adoption and self-learning, while the remaining 16.6% is explained by other factors beyond the research model.